Emplacement Temperature of the Overbank and Dilute-Detached Pyroclastic Density Currents of Merapi 5 November 2010 Events using Reflectance Analysis of Associated Charcoal - Haryo Edi Wibowo; Anggun Purnama Edra; Agung Harijoko; Ferian Anggara (Journal of Applied Geology, 2018)
Merapi eruption in 2010 produced 17 km high column of ash and southward pyroclastic density current (PDC). Based on the deposits characteristics and distributions, the PDC is divided into channel and overbank facies (pyroclastic flow), and associated diluted PDC (pyroclastic surge). The hot overbank PDCs and the associated dilute-detached PDCs are the main cause of high casualty (367 fatalities) in medial-distal area (5–16 km), especially near main valley of Kali Gendol. We reported the emplacement temperature of these two deposits using reflectance analysis of charcoal. We used both entombed charcoals in the overbank PDC and charcoals in singed house nearby. Samples were collected on 6–13 km distance southward from summit. Charcoalification temperatures of the entombed charcoals represent deposition temperature of the overbank PDCs, whereas those of charcoals in the singed house resembles temperature of the associated dilute-detached PDCs. Results show mean random reflectance (Ro%) values of entombed charcoal mainly range 1.1–1.9 correspond to temperature range 328–444 °C, whereas charcoal in singed house range 0.61–1.12 with estimated temperature range 304–358 °C. The new temperature data of the dilute-detached PDCs in the medial-distal area is crucial for assessing impact scenarios for exposed populations as it affects them lethally and destructively